Determination of the Natural Radioactivity in Soil Of Al-Amirya Region - Jumana Thaer Abdulkareem Ibrahim; Ahmed Mundher Shaheed Naji; Mahmoud Ghanem Thajeel Haddad (Genius Journals, 2024)
For studying and analyzing the radiation background for Al-Amirya city in Baghdad, Iraq, using nuclear and spectroscopic method, 10 samples of surface soil were collected. The natural specific radioactivity of radioactive (226Ra, 226Th, 40K) in soil were determined using Sodium Iodide detector. The detector was surrounded from all directions by thick lead layer of 10 cm and container made of three plates of aluminum, copper and iron to prevent the effect of background degradation. The relationship between Radium (Ra) equivalent, external Hazard (Hex), internal Hazard (Hin) and gamma level index (lyr) as a function of absorbed dose was studied it was found to be linear The study identified that many nuclides as an equivalent activity for 226Ra, 228 Ac. The results for 226Ra, 40K and 228 Ac were 0.069, 6.864 and 4.0499 Bq/kg respectively for soil.The results showed that the specific activity of radioactive nuclides in most samples is normal and within the allowed limits. The results were in a good agreement with international specifications . Our results indicate that the natural radioactive (Background) in Al- Amirya region for soil is normal.
Keywords: Natural; Radioactivity; Soil